Differential Impact of Dietary Branched Chain and Aromatic Amino Acids on Chronic Kidney Disease Progression in Rats - Pillai, Samyuktha Muralidharan; Herzog, Brigitte; Seebeck, Petra; Pellegrini, Giovanni; Roth, Eva; Verrey, François (Frontiers in Physiology, 2019)
The metabolism of dietary proteins generates waste products that are excreted by the kidney, in particular nitrogen-containing urea, uric acid, ammonia, creatinine and other metabolites such as phosphates, sulfates and protons. Kidney adaptation includes an increase in renal plasma flow (RPF) and glomerular filtration rate (GFR) and represents a burden for diseased kidneys increasing the progression rate of CKD. The present study aimed at identifying potential differences between amino acid (AA) groups constituting dietary proteins regarding their impact on RPF, GFR and CKD progression. We utilized the well-established 5/6th nephrectomy (5/6 Nx) CKD model in rats and submitted the animals for 5 weeks to either the control diet (18% casein protein) or to diets containing 8% casein supplemented with 10% of a mix of free amino acids, representing all or only a subset the amino acids contained in casein. Whereas the RPF and GFR measured in free moving animals remained stable during the course of the diet in rats receiving the control mix, these parameters decreased in animals receiving the branched chain amino acid (BCAA) supplementation and increased in the ones receiving the aromatic amino acids (AAAs). In animals receiving essential amino acids (EAAs) containing both BCAAs and AAAs, there was only a small increase in RPF. The kidneys of the 5/6 Nx rats receiving the BCAA diet showed the strongest increase in smooth muscle actin and collagen mRNA expression as a result of higher level of inflammation and fibrosis. These animals receiving BCAAs also showed an increase in plasma free fatty acids pointing to a problem at the level of the energy metabolism. In contrast, the animals under AAA diet showed an activation of AMPK and STAT3. Taken together, our results demonstrate that subsets of EAAs contained in dietary proteins, specifically BCAAs and AAAs, exert contrasting effects on kidney functional parameters and CKD progression.